D8-poly(methyl methacrylate)-poly[(oligo ethylene glycol) methyl ether methacrylate] tri-block-copolymer electrolytes: Morphology, conductivity and battery performance. (22nd November 2017) - Bergfelt, Andreas; Rubatat, Laurent; Mogensen, Ronnie; Brandell, Daniel; Bowden, Tim
Abstract: A series of deuterated tri-block copolymers with the general structure d8 -PMMA-POEGMA-d8 -PMMA, with variation in d8 -PMMA chain length, were synthesized using sequential controlled radical polymerization (ATRP). Solid polymer electrolytes (SPEs) were produced by blending tri-block copolymers and lithium bis(trifluoro methylsulfonate) (LiTFSI). Small-angle neutron scattering (SANS) was used to study the bulk morphology of the deuterated tri-block copolymer electrolyte series at 25 °C, 60 °C and 95 °C. The lack of a second Tg in DSC analysis together with modelling with the random phase approximation model (RPA) confirmed that the electrolytes are in the mixed state, with negative Flory-Huggins interaction parameters. AC impedance spectroscopy was used to study the ionic conductivity of the SPE series in the temperature interval 30 °C–90 °C, and a battery device was constructed to evaluate a 25 wt% d8 -PMMA electrolyte. The Li | SPE | LiFePO4 cell cycled at 60 °C, giving a discharge capacity of 120 mAh g −1, while cyclic voltammetry showed that the SPE was stable at 60 °C. Graphical abstract: Highlights: Synthesis of a deuterated tri-block copolymer. Small-angle neutron scattering characterization of solid polymer electrolytes. Study of the electrochemical and battery performance of solid polymer electrolytes.